Проєктування локальної мережі підземної лікарні - Усов, О. О.; Штих, І. А. (ХНУРЕ, 2023)
This work is devoted to the construction of a local network of underground critical infrastructure, namely, the construction of a local network of an underground hospital is considered. The main principles of the underground type of network construction are considered. An analysis of the complex conditions in which this network will have to be built and the most effective options for equipment and location of vulnerable network objects has been carried out. The relevance of this building for the city of Kharkiv is also considered. It has been established that under such conditions, such a wired connection of the entire network is the most efficient and will be able to quickly process all available information.
Keywords: медична інфраструктура; безперебійний зв’язок; медичні заклади; локальні мережі